Soccer Barras, Passions and Capital in Colombia (Palimpsesto, 2022)
Two tendencies stand out in the growing body of literature on the relationship between “barras futboleras” and violence: on the one hand, the identity and ethnographic emphasis of those works. On the other hand, although the relationship between soccer and economics is a facet explored in the academic literature, economy does not appear as a category of study of the “barras futboleras”. This article departs from these tendencies and moves away from the description of identities to explore the interactions between actors in the light of the psychoanalytic notion of collective narcissism and the critique of familism using contemporary French philosophy. It also maps some of the interactions of the “barras futboleras” with public and private actors in light of the collapse of the railing of the North Stand at the El Campin Stadium in Bogota in 1998. The economy or, more specifically, capitalism, is the thread that binds these interactions between actors, outside their identities, in the game of relations and powers between the family, the private companies and the State.
Keywords: Barras futboleras; Violences; Participation; collective narcissism; families